Transcriptome analysis of the genes regulating phytohormone and cellular patterning in Lagerstroemia plant architecture. Issue 1 (December 2018) - Ju, Yiqian; Feng, Lu; Wu, Jiyang; Ye, Yuanjun; Zheng, Tangchun; Cai, Ming; Cheng, Tangren; Wang, Jia; Zhang, Qixiang; Pan, Huitang
Abstract Plant architecture is a popular research topic because plants with different growth habits that may generate economic or ornamental value are in great demand by orchards and nurseries. However, the molecular basis of the architecture of woody perennial plants is poorly understood due to the complexity of the phenotypic and regulatory relationships. Here, transcriptional profiling of dwarf and non-dwarf crapemyrtles was performed, and potential target genes were identified based on the phenotype, histology and phytohormone metabolite levels. An integrated analysis demonstrated that the internode length was explained mainly by cell number and secondarily by cell length and revealed important hormones in regulatory pathway ofLagerstroemia architecture. Differentially expressed genes (DEGs) involved in phytohormone pathways and cellular patterning regulation were analysed, and the regulatory relationships between these parameters were evaluated at the transcriptional level. Exogenous indole-3-acetic acid (IAA) and gibberellin A4 (GA4 ) treatments further indicated the pivotal role of auxin in cell division within the shoot apical meristem (SAM) and suggested an interaction between auxin and GA4 in regulating the internode length ofLagerstroemia . These results provide insights for further functional genomic studies on the regulatory mechanisms underlyingLagerstroemia plant architecture and may improve the efficiency of woody plant molecular breeding.